DIVERSIFICATION OF THE ACTIVITY OF THE HOTEL AND RESTAURANT ENTERPRISE AS A WAY OF INCREASING COMPETITIVENESS - Lykholat, O. A.; Vyshnikina, O. V.; Apalkova, D. K. (Systems and Technologies, 2023)
The article emphasizes that the diversification strategy as a growth strategy is widely used in the field of temporary accommodation and catering. In order to obtain a complete picture of the effectiveness of the diversification of the enterprise, it is necessary to carefully analyze all subsystems of the enterprise that were affected by the project of diversification of activities, namely financial, economic, production, technological, informational, and in addition, it is necessary to take into account the impact on the external environment of the enterprise, especially markets, on which it works, and consumer loyalty. Therefore, the evaluation of the effectiveness of the diversification of the enterprise’s activities can be implemented only if the responsible manager or department of the enterprise has a certain system of indexes. The main groups of indexes are financial and economic, production and technological, market. Taken together, all the above indexes provide a comprehensive assessment of the effectiveness of diversification of the company’s activities in the field of temporary accommodation and catering. The presence of a single formalized system of indexes can facilitate the process of analyzing the effectiveness of the project of implementing diversification of activities at the enterprise. In addition, this system of indexes should be taken into account in the economic service of the enterprise and used in the economic management system. To determine whether diversification is really justified, entrepreneurs need to clearly define the algorithm of actions. The proposed algorithm consists of five steps, each step determines the required number of actions, sufficient to implement each subsequent step in the process of implementing the diversification strategy at the enterprise. Thus, before making a decision to diversify the hotel, the owner must analyze the current situation from the point of view of the viability of the existing business. The most effective will be the choice of that direction, which, on the one hand, is more familiar and quite effective for the entrepreneur, and on the other hand, will allow to bring the enterprise to a new qualitative level with the lowest costs in order to acquire competitive advantages in the market.